The Concussion Challenge Assessment: Development and reliability of a novel gross motor assessment tool for paediatric concussion - Tanel, Michelle R.; Gupta, Christopher; Wilson, Katherine E.; Murphy, James; Wright, F. Virginia; Reed, Nick (Frontiers in Sports and Active Living, 2022)
Aims The aim of this study was to develop a gross motor performance clinical assessment tool, the Concussion Challenge Assessment (CCA), for paediatric concussion populations. Methods An expert panel evaluated tasks from the Acquired Brain Injury Challenge Assessment to determine relevant tasks for a paediatric concussion population. These tasks were administered to a convenience sample of 854 healthy youth. An analysis of the response options for each task, considering task difficulty, was performed. The test–retest reliability of each task was considered to finalise the tool. Results The Acquired Brain Injury Challenge Assessment was reduced to six tasks (three coordination, two speed and agility, and one strength) to create the CCA. Population-specific 4-point response options were generated, which, upon examination of task difficulty, were revised as 5-point response sets to better capture performance differences. The test–retest reliability results led to acceptance of all six: three performance tasks and three exertion tasks. Conclusion This development of the CCA is an important step in creating a gross motor performance assessment tool that can assist in the determination of when youth are able to safely return to activity following a concussion.